Penentuan teknologi pengolahan sampah menjadi energi di Kabupaten Boyolali dengan Analytic Hierarchy Process (AHP) - Novica Ayu Sari; Mayang Ananda Rini; Whindy Ndaru Oktaviani; Rarastika Nur Ghaida; Mega Mutiara Sari; I Wayan Koko Suryawan (Universitas Riau, 2022)
The waste composition in Boyolali Regency consists of 37.13% garden waste. The waste can be treated with a thermal process so that it can be reused for energy. The method of sorting waste with thermal technology consists of various types adapted to the gods. This study aimed to evaluate the most co-cog heat treatment processes for waste processing in Boyolali Regency. The determination process is carried out using a literature review, while the selection process uses the Analytical Hierarchy Process (AHP) method. The alternatives given in this research are carbonization, pyrolysis, and synergy processes. In the alternative selection, there are three criteria, namely mass balance, CO2 residue, and energy volatility. In terms of mass balance, the waste that the carbonization process can treat tends to be higher than that of the pyrolysis and incineration processes. Meanwhile, the carbonization process is better than pyrolysis and carbonization for wood waste for emission and energy requirements. The result of AHP shows that the carbonization process is suitable to be applied in Boyolali Regency. However, it is necessary to conduct further studies on non-technical aspects to strengthen alternative election results.